Pembuatan Animasi Game Pemasangan NGT sebagai Media Pembelajaran Praktikum KDM - Siscadarsih, Indraswari; Ramadhani, Devy Kurnia; Dewi, Nur Indah Kusuma (Jurnal Pengelolaan Laboratorium Pendidikan, 2024)
The competence of a midwife has a major influence on the quality of midwifery services provided. The Midwifery education program structure contains 40% theory and 60% practice. Background: During the COVID-19 pandemic, there has been a rapid and drastic change in health education. With the restrictions during the pandemic, student access to the laboratory is also hampered. Objective: This research allows the creation of new learning media based on game animation that can provide students with a real audio-visual picture of a particular midwifery care procedure. Methods: The design of this research is Research and Development (Research and Development). The development research model used is ADDIE with the stages of Analysis, Design, Development and, Production, Implementation, Evaluation. The data collection method used in this study was means of observation and questionnaires. Tests in this study were conducted to test the usability aspect. Results: This application can be used on Windows-based personal computers and Android-based mobile phones. The results of testing the usability quality of the NGT installation game application are 91.56% and get a very good predicate so that this application can be used for practical learning. Conclusion: The NGT installation game application can be used as a KDM practicum learning media.